Dielectric composition and electronic component
Patent Information
- Application Number
- JP2023133534
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-18
- Publication Date
- 2025-03-03
AI Technical Summary
【0007】 本発明者らは、熱衝撃などによるクラックを抑制することができる誘電体組成物について鋭意検討した結果、RE-Mg-Ti-O偏析粒子を有する誘電体組成物が、クラック抑制に優れた効果を有することを見出し、本発明を完成させるに至った。
Smart Images

Figure 2025028615000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a dielectric composition and an electronic component including a dielectric layer formed from the dielectric composition. [Background technology]
[0002] Electronic circuits or power circuits incorporated in electronic devices are equipped with many electronic components such as multilayer ceramic capacitors that utilize the dielectric properties exhibited by dielectrics. Patent Document 1 discloses that the main component of the dielectric ceramic of the electronic components is a composition represented by the general formula ABO3 (wherein A is at least one of Ba, Sr, Ca, and Mg, and B is at least one of Ti, Zr, and Hf).
[0003] Conventional electronic components, as shown in Patent Document 1, are mounted on circuit boards and the like by methods such as "reflow soldering" and "flow soldering." Although "flow soldering" has the advantage of being less costly than "reflow soldering," when mounted on a board by "flow soldering," cracks may occur in the dielectric composition (dielectric ceramic) of the electronic components due to thermal shock and the like. For this reason, there is a demand for the development of a dielectric composition that can effectively prevent cracks due to thermal shock and the like. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2001-6966 A Summary of the Invention [Problem to be solved by the invention]
[0005] The present invention has been made in view of the above circumstances, and has an object to provide a dielectric composition capable of suppressing cracks caused by thermal shock or the like. [Means for solving the problem]
[0006] In order to achieve the above object, the dielectric composition according to the present invention comprises: A dielectric composition comprising main phase particles and segregated particles, at least a part of the segregated particles is RE-Mg-Ti-O segregated particle containing RE element, Mg, Ti and O, The RE element is a rare earth element, the total amount of the RE element, Mg and Ti contained in the RE-Mg-Ti-O segregated particles is 70 parts by mol or more when the total amount of the metal elements contained in the RE-Mg-Ti-O segregated particles is 100 parts by mol, The ratio of Mg to the total of the RE element and Mg in the RE-Mg-Ti-O segregated particles is 0.1 to 0.3.
[0007] The present inventors conducted extensive research into dielectric compositions capable of suppressing cracks caused by thermal shock and the like, and as a result found that a dielectric composition having RE-Mg-Ti-O segregated particles has an excellent effect in suppressing cracks, thereby completing the present invention.
[0008] The reason why the RE-Mg-Ti-O segregated particles are able to suppress cracks due to thermal shock and other factors is not entirely clear. However, it is thought that, for example, the RE-Mg-Ti-O segregated particles suppress excessive grain growth of the main phase particles.
[0009] Furthermore, even if cracks were to occur in the dielectric composition, it is believed that the progression of the cracks would be stopped when the cracks reach the RE-Mg-Ti-O segregated particles.
[0010] The RE-Mg-Ti-O segregated particles may be present at the grain boundaries of the main phase particles.
[0011] Preferably, the RE-Mg-Ti-O segregated particles have an average particle size of 0.1 μm or less.
[0012] Preferably, the cross section of the dielectric composition is 5 μm in total. 2When observing the above, The RE-Mg-Ti-O segregated particles are 0.2 to 2 particles / μm on average. 2 To be observed.
[0013] By reducing the size of the RE-Mg-Ti-O segregated particles and increasing their surface area, the surface energy can be increased, so that even a small amount of RE-Mg-Ti-O segregated particles can effectively suppress the migration of the grain boundaries of the main phase particles and further suppress the excessive grain growth of the main phase particles, making it more difficult for cracks to occur.
[0014] In addition, since the amount of RE-Mg-Ti-O segregated particles is small, they do not completely block the spaces between the main phase particles, which facilitates heat conduction between the main phase particles, and the dielectric composition as a whole has a high thermal conductivity and is resistant to thermal shock. As a result, cracks due to thermal shock can be further suppressed.
[0015] Furthermore, when the average number of the RE-Mg-Ti-O segregated particles is within the above range, a higher dielectric constant can be maintained than when the average number exceeds the above range. When the average number of the RE-Mg-Ti-O segregated particles is within the above range, the main phase particles that mainly exert the dielectric properties are sufficiently present in the dielectric composition, which is considered to result in a high dielectric constant.
[0016] Preferably, the composition of the main phase particles is BaTiO3.
[0017] Preferably, the composition of the RE-Mg-Ti-O segregated particles is {RE (1-a) Mg a}2Ti2O 7-a and The a is 0.1 to 0.3.
[0018] The electronic component of the present invention comprises a dielectric layer containing the dielectric composition of the present invention. [Brief description of the drawings]
[0019] [Figure 1A]FIG. 1A is a cross-sectional view of a multilayer ceramic capacitor according to one embodiment of the present invention. [Figure 1B] FIG. 1B is a cross-sectional view of the multilayer ceramic capacitor taken along line IB-IB in FIG. 1A. [Diagram 2] FIG. 2 is a schematic diagram of a cross section of a dielectric composition according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] < Multilayer Ceramic Capacitors > A multilayer ceramic capacitor 1 as an example of an electronic component according to this embodiment is shown in Figures 1A and 1B. The multilayer ceramic capacitor 1 has an element body 10 in which dielectric layers 2 and internal electrode layers 3 are alternately laminated. A pair of external electrodes 4 are formed on both ends of the element body 10, and are electrically connected to the internal electrode layers 3 arranged alternately inside the element body 10. There is no particular restriction on the shape of the element body 10, but it is usually a rectangular parallelepiped. There is also no particular restriction on the dimensions of the element body 10, and the dimensions may be appropriate depending on the application.
[0021] In this embodiment, the vertical dimension L0 (see FIG. 1A) of the element body 10 is preferably 3.5 to 0.4 mm. In this embodiment, the width dimension W0 (see FIG. 1B) of the element body 10 is preferably 2.7 to 0.2 mm.
[0022] Specific sizes of the element body 10 include L0×W0 of (3.2±0.3) mm×(2.5±0.2) mm, (3.2±0.3) mm×(1.6±0.2) mm, (2.0±0.2) mm×(1.2±0.1) mm, (1.6±0.2) mm×(0.8±0.1) mm, (1.0±0.1) mm×(0.5±0.05) mm, (0.6±0.06) mm×(0.3±0.03) mm, (0.4±0.04) mm×(0.2±0.02) mm, etc. H0 is not particularly limited, and is, for example, approximately equal to or less than W0.
[0023] The dielectric layer 2 is made of a dielectric composition according to the present embodiment, which will be described later.
[0024] The thickness of each dielectric layer 2 (interlayer thickness) is not particularly limited and can be set arbitrarily depending on the desired characteristics, applications, etc. Usually, the interlayer thickness is preferably 30 μm or less, more preferably 10 μm or less, and further preferably 5 μm or less. The number of laminated dielectric layers 2 is not particularly limited, but in this embodiment, it is preferably 20 or more.
[0025] In this embodiment, the internal electrode layers 3 are laminated so that their ends are alternately exposed on the surfaces of two opposing end faces of the element body 10.
[0026] The thickness of the internal electrode layer 3 is not particularly limited, but is, for example, 2 μm or less, and preferably 1.5 μm or less.
[0027] The conductive material contained in the internal electrode layer 3 is not particularly limited. Examples of precious metals used as conductive materials include Pd, Pt, and Ag-Pd alloys. Examples of base metals used as conductive materials include Ni, Ni-based alloys, Cu, and Cu-based alloys. Note that Ni, Ni-based alloys, Cu, or Cu-based alloys may contain various trace components such as P and / or S at about 0.1 mass% or less. The internal electrode layer 3 may be formed using a commercially available electrode paste. The thickness of the internal electrode layer 3 may be appropriately determined depending on the application, etc.
[0028] There is no particular limitation on the conductive material contained in the external electrodes 4. For example, known conductive materials such as Ni, Cu, Sn, Ag, Pd, Pt, Au, alloys of these, conductive resins, etc. may be used. The thickness of the external electrodes 4 may be appropriately determined depending on the application, etc.
[0029] < Dielectric Composition > 2, the dielectric composition constituting the dielectric layer 2 includes main phase grains 20 and RE-Mg-Ti-O segregated grains 22. The RE-Mg-Ti-O segregated grains 22 include an RE element, Mg, Ti, and O. Here, the "RE element" means a rare earth element. The RE-Mg-Ti-O segregated grains 22 may be present at grain boundaries 28 of the main phase grains 20.
[0030] In this embodiment, it is sufficient that at least a part of the segregated particles contained in the dielectric composition are the RE-Mg-Ti-O segregated particles 22, and the dielectric composition may contain segregated particles having a composition other than the RE-Mg-Ti-O segregated particles 22.
[0031] < Main phase particles > The main phase particle 20 of the present embodiment contains a compound represented by AMO3 as a main component. Note that the main component of the main phase particle 20 is a component that occupies 80 to 100 parts by mass, and preferably 90 to 100 parts by mass, when the main phase particle 20 is taken as 100 parts by mass.
[0032] The molar ratio of the A element to the M element, represented by (molar ratio of A / molar ratio of M), may or may not be 1. (molar ratio of A / molar ratio of M) is preferably 0.9 to 1.2.
[0033] The element A includes at least one selected from Ba and Ca. The element A is preferably Ba. This allows the dielectric composition to exhibit a higher relative dielectric constant.
[0034] Furthermore, when the A element is Ba and Ca, the content of Ba is preferably 0.9 to 1 part by mol when the total of Ba and Ca is 1 part by mol.
[0035] The M element includes at least one selected from Ti and Zr. The M element is preferably Ti. This allows the dielectric composition to exhibit a higher relative dielectric constant.
[0036] Furthermore, when the M element is Ti and Zr, the content of Ti is preferably 0.8 to 1 part by mol when the total amount of Ti and Zr is 1 part by mol.
[0037] The main phase particles 20 may further include Mg, Mn, Cr, Si, RE elements, V, Li, B, Al, and the like.
[0038] < RE-Mg-Ti-O segregated particles > The RE-Mg-Ti-O segregated particles 22 contain the RE elements, Mg, Ti and O.
[0039] "RE element" refers to a rare earth element. The type of RE element is not particularly limited, but for example, Y, Dy or Ho can be used. The RE element may be used alone or in combination of two or more kinds.
[0040] When the total amount of metal elements contained in the RE-Mg-Ti-O segregated particles 22 is taken as 100 parts by mol, the total amount of the RE element, Mg and Ti contained in the RE-Mg-Ti-O segregated particles 22 is 70 parts by mol or more.
[0041] In the RE-Mg-Ti-O segregated particles 22, the ratio of Mg to the total of the RE element and Mg {Mg / (RE+Mg)} is 0.1 to 0.3.
[0042] The ratio of Ti to the total of the RE element and Mg in the RE-Mg-Ti-O segregated particles 22 {Ti / (RE+Mg)} is preferably 0.7 to 1.3.
[0043] The composition of the RE-Mg-Ti-O segregated particles 22 is not particularly limited. For example, (1-a) Mg a}2Ti2O 7-a a may be 0.1 to 0.3.
[0044] The average particle size of the RE-Mg-Ti-O segregated particles 22 is preferably 0.1 μm or less, and more preferably 0.05 μm or less, and may be the average of the circle-equivalent diameters of the RE-Mg-Ti-O segregated particles 22.
[0045] The cross section of the dielectric composition is 5 μm in total. 2 When observed as above, the RE-Mg-Ti-O segregated particles 22 were found to be 0.2 to 2 particles / μm on average. 2 It is preferable to observe 0.5 to 1.5 particles / μm. 2 It is more preferable to observe the cross section of the dielectric composition in a total area of 5 μm 2 When observing more than 5 μm, the observation field is 1. 2 When two or more visual fields are observed, the total area of each visual field must be less than 5 μm 2 or more, when observed in each visual field.
[0046] Note that the RE-Mg-Ti-O segregated particle 22 that is entirely contained within one field of view is counted as one particle. For example, an RE-Mg-Ti-O segregated particle 22 that is located at the edge of the field of view and is observed as being partially missing is not counted.
[0047] The RE-Mg-Ti-O segregated particles 22 preferably have a tetragonal crystal system.
[0048] The space group of the RE-Mg-Ti-O segregated particles 22 is
number
[0049] < How to check for segregated particles > The method for determining whether or not the dielectric composition constituting the dielectric layer 2 contains the RE-Mg-Ti-O segregated particles 22 is not particularly limited, but a specific example of the method will be described below.
[0050] First, a cross section of the dielectric composition is photographed using a scanning transmission electron microscope (STEM) to obtain a dark field (DF) image. The size of the photographed field is not particularly limited, but is, for example, about 1 to 10 μm square. In this dark field image, a region having a contrast different from that of the main phase particles 20 is recognized as a different phase. The judgment of whether or not there is a different contrast, i.e., whether or not there is a different phase, may be made visually, or may be made by using software for performing image processing, or the like.
[0051] Then, the various elements in the heterogeneous phase are measured by energy dispersive X-ray analysis (EDS analysis).
[0052] When the RE element, Mg, Ti and O are present at the same position in the heterogeneous phase, the total of the RE element, Mg and Ti in the heterogeneous phase is 70 molar parts or more when the total of the metal elements in the heterogeneous phase is 100 molar parts, and Mg / (RE+Mg) in the heterogeneous phase is 0.1 to 0.3, the heterogeneous phase can be determined to be RE-Mg-Ti-O segregated particles 22.
[0053] In addition, it can be determined that they are RE-Mg-Ti-O segregated particles 22 from the element mapping image.
[0054] < Manufacturing method of multilayer ceramic capacitor > Next, an example of a method for manufacturing the multilayer ceramic capacitor 1 shown in FIGS. 1A and 1B will be described below.
[0055] In this embodiment, a calcined powder of AMO3, which is the main component of the main phase particles 20 constituting the above-mentioned dielectric composition, and a calcined powder of a raw material mixture of the RE-Mg-Ti-O segregated particles 22 are prepared.
[0056] The calcined powder of AMO3 is a calcined powder of the A element and the M element that constitute the main phase particles 20 after sintering.
[0057] The calcined powder of the raw material mixture of the RE-Mg-Ti-O segregated particles 22 is a calcined powder of the RE elements, Mg, and Ti that constitute the RE-Mg-Ti-O segregated particles 22 after firing.
[0058] The raw materials of the above elements are not particularly limited, and oxides of the above elements can be used. In addition, various compounds that can give oxides of the above elements by firing can be used. Examples of the various compounds include carbonates, oxalates, nitrates, hydroxides, and organometallic compounds. In this embodiment, the above starting materials are preferably powders.
[0059] Among the prepared starting materials, the raw materials of the AMO3 particles are weighed in a predetermined ratio, and then wet-mixed for a predetermined time using a ball mill or the like. The mixed powder is dried, and then heat-treated in the air at a temperature range of 700 to 1300°C to obtain a calcined powder of the raw material mixture of the AMO3 particles. The calcined powder may also be pulverized for a predetermined time using a ball mill or the like.
[0060] After firing, various compounds such as oxides of the elements constituting the RE-Mg-Ti-O segregated particles 22 are prepared, heat-treated, and then pulverized for a predetermined time using a ball mill or the like to obtain a calcined powder of the raw material mixture of the RE-Mg-Ti-O segregated particles 22.
[0061] For example, the particle size of the RE-Mg-Ti-O segregated particles 22 can be changed by changing the grinding time, and the longer the grinding time, the smaller the particle size of the RE-Mg-Ti-O segregated particles 22. In addition, the particle size of the RE-Mg-Ti-O segregated particles 22 can be changed by changing the media diameter of the ball mill.
[0062] Next, a paste for producing a green chip is prepared. The calcined powder of the raw material mixture of the obtained AMO3 particles, the calcined powder of the raw material mixture of the RE-Mg-Ti-O segregated particles 22, a binder, and a solvent are kneaded to form a paint, and a paste for the dielectric layer is prepared. The binder and the solvent may be publicly known.
[0063] The dielectric layer paste may contain additives such as a plasticizer and a dispersant, if necessary.
[0064] The internal electrode layer paste is obtained by kneading the above-mentioned conductive material, a binder, and a solvent. The binder and the solvent may be known. The internal electrode layer paste may contain additives such as a co-material and a plasticizer as necessary.
[0065] The external electrode paste can be prepared in the same manner as the internal electrode layer paste.
[0066] Each of the obtained pastes is used to form a green sheet, an internal electrode pattern is formed on the green sheet, and these are laminated to obtain a laminate, which is then cut to obtain green chips.
[0067] The obtained green chip is subjected to a binder removal treatment as necessary. The binder removal treatment conditions are, for example, a holding temperature of preferably 200 to 350°C.
[0068] After the binder removal process, the green chip is fired to obtain the element body 10. In this embodiment, the atmosphere during firing is not particularly limited, and may be in air or a reducing atmosphere. In this embodiment, the holding temperature during firing is not particularly limited, and is, for example, 1200 to 1350°C.
[0069] After firing, the obtained element body 10 is subjected to a reoxidation treatment (annealing) as necessary. The annealing conditions are preferably, for example, an oxygen partial pressure during annealing higher than that during firing, and a holding temperature of 1150° C. or less.
[0070] The dielectric composition constituting the dielectric layer 2 of the element body 10 obtained as described above is the dielectric composition described above. The end faces of this element body 10 are polished, and an external electrode paste is applied and baked to form the external electrodes 4. Then, if necessary, a coating layer is formed on the surface of the external electrodes 4 by plating or the like.
[0071] In this manner, the multilayer ceramic capacitor 1 according to this embodiment is manufactured.
[0072] < Summary of this embodiment > One of the causes of cracks in the dielectric composition is "excessive grain growth of the main phase particles 20." That is, excessive grain growth of the main phase particles 20 makes it easier for pores to form in the intra-dielectric composition, and cracks may occur starting from the pores when a thermal shock is applied by, for example, "flow soldering."
[0073] For this reason, in order to suppress cracks in the dielectric composition, it is desirable to suppress excessive grain growth of the main phase grains 20.
[0074] One method for suppressing excessive grain growth of the main phase particles 20 is to use the "pinning effect of second phase particles." Here, the "pinning effect" refers to a phenomenon in which the grain growth of first phase particles (main phase particles 20 in this embodiment) is suppressed by suppressing the movement of grain boundaries 28 by second phase particles. For this reason, the present inventors have investigated a method of making particles that will become second phase particles exist in the dielectric composition.
[0075] First, RE2O3 and MgO, when used alone, tend to form solid solutions in AMO3, and may dissolve in AMO3. For this reason, when used alone, RE2O3 and MgO are unlikely to exist as second phase particles that exert a pinning effect in the dielectric composition.
[0076] Furthermore, RE2O3 and MgO form a solid solution, with MgO replacing part of RE2O3 and part of MgO replacing RE2O3, but they do not form any other compounds. Therefore, similar to the behavior of simple substances RE2O3 and MgO, the solid solution of RE2O3 and MgO also dissolves in AMO3, and therefore the solid solution of RE2O3 and MgO is also unlikely to exist as second phase particles that exert a pinning effect in the dielectric composition.
[0077] Therefore, the present inventors have found that the second phase particles are formed by forming RE-Mg-Ti-O segregated particles 22 from RE2O3, MgO and TiO2. Since the RE-Mg-Ti-O segregated particles 22 are a stable compound, it is considered that they are unlikely to dissolve in the main phase particles 20 mainly composed of AMO3. Therefore, the presence of the RE-Mg-Ti-O segregated particles 22 at the grain boundaries 28 of the main phase particles 20 can efficiently suppress the movement of the grain boundaries 28 of the main phase particles 20 due to a pinning effect, and the grain growth of the main phase particles 20 can be suppressed. As a result, it is possible to make it difficult for cracks to occur due to thermal shock or the like.
[0078] Even if a crack occurs in the dielectric composition, the progression of the crack is stopped when the crack reaches the RE-Mg-Ti-O segregated particles 22. That is, the progression of the crack can be stopped by the RE-Mg-Ti-O segregated particles 22.
[0079] Furthermore, since the surface energy can be increased by finely dividing the RE-Mg-Ti-O segregated particles 22 and increasing their surface area, even a small amount of the RE-Mg-Ti-O segregated particles 22 present between the main phase particles 20 can effectively suppress the movement of the grain boundaries 28 of the main phase particles 20 and suppress the grain growth of the main phase particles 20, making it difficult for cracks to occur, and the RE-Mg-Ti-O segregated particles 22 can stop the progression of the cracks.
[0080] Furthermore, when the amount of the RE-Mg-Ti-O segregated particles 22 is small, the gaps between the main phase particles 20 are not completely blocked, which facilitates heat conduction between the main phase particles 20, and the dielectric composition as a whole has high thermal conductivity and is resistant to thermal shock. As a result, cracks due to thermal shock can be further suppressed.
[0081] Although the embodiment of the present invention has been described above, the present invention is not limited to the above embodiment, and may be modified in various aspects within the scope of the present invention.
[0082] In the above-described embodiment, the electronic component according to the present invention has been described as a multilayer ceramic capacitor. However, the electronic component according to the present invention is not limited to a multilayer ceramic capacitor and may be any electronic component having the above-described dielectric composition.
[0083] For example, it may be a single-plate ceramic capacitor in which a pair of electrodes are formed on the above-mentioned dielectric composition. EXAMPLES
[0084] The present invention will be described in more detail below using examples and comparative examples, although the present invention is not limited to the following examples.
[0085] Powders of BaCO3, CaCO3, ZrO2, and TiO2 were prepared as starting materials for the main phase particles 20 contained in the dielectric composition. The prepared starting materials were weighed so that the main components of the main phase particles 20 after firing would be as shown in Tables 1, 2, and 4.
[0086] Next, the weighed powders were wet-mixed in a ball mill for 16 hours using ion-exchanged water as a dispersion medium, and the mixture was dried to obtain a mixed raw material powder. The mixed raw material powder obtained was then heat-treated in air at a holding temperature of 1000°C for a holding time of 2 hours, and wet-pulverized in a ball mill for 16 hours using ion-exchanged water as a dispersion medium, and the mixture was dried to obtain a calcined powder of the raw material mixture of the main phase particles 20.
[0087] Powders of an oxide of the RE element (Y2O3), MgCO3, and TiO2 were prepared as raw materials for the RE-Mg-Ti-O segregated particles 22. The prepared starting materials were weighed out so that the "Ti / (RE+Mg)" and "Mg / (RE+Mg)" of the RE-Mg-Ti-O segregated particles 22 were as shown in Tables 1, 2, and 4, and the amount of calcined powder of the raw material mixture of the RE-Mg-Ti-O segregated particles 22 added (unit: parts by mass) (shown as "addition amount" in Tables 1, 2, and 4) was as shown in Tables 1, 2, and 4, relative to 100 parts by mass of the calcined powder of the raw material mixture of the main phase particles 20.
[0088] Powders of the oxide of the RE element (Y2O3), MgCO3, and TiO2 were prepared as raw materials for the RE-Mg-Ti-O segregated particles 22. The prepared powders were weighed so that the “Ti / (RE+Mg)” and “Mg / (RE+Mg)” of the RE-Mg-Ti-O segregated particles 22 were as shown in Tables 1, 2, and 4.
[0089] Next, the weighed powders were wet-mixed in a ball mill for 16 hours using ion-exchanged water as a dispersion medium, the mixture was dried, and heat-treated in air at a holding temperature of 1000°C for a holding time of 2 hours. The mixture was wet-pulverized in a ball mill for 16 hours using ion-exchanged water as a dispersion medium, and the mixture was dried to obtain a calcined powder of the raw material mixture of RE-Mg-Ti-O segregated particles 22.
[0090] Furthermore, inorganic additives were prepared by the following method. First, MgCO3, Y2O3, MnCO3, SiO2, and V2O5 powders were wet-mixed in a ball mill for 16 hours using ion-exchanged water as a dispersion medium to obtain a mixture. Next, the mixture was dried and heat-treated in air at a holding temperature of 900°C for 2 hours. The heat-treated mixture was wet-ground in a ball mill for 16 hours using ion-exchanged water as a dispersion medium, and then dried to obtain an inorganic additive.
[0091] Next, the calcined powder of the raw material mixture of the main phase particles 20, the calcined powder of the raw material mixture of the RE-Mg-Ti-O segregated particles 22, inorganic additives, a binder, and a solvent were kneaded together to form a paint, to prepare a paste for the dielectric layer. Here, the prepared starting materials were weighed out so that the added amount (unit: parts by mass) of the calcined powder of the raw material mixture of the RE-Mg-Ti-O segregated particles 22 (referred to as "addition amount" in Tables 1, 2, and 4) per 100 parts by mass of the calcined powder of the raw material mixture of the main phase particles 20 was as shown in Tables 1, 2, and 4.
[0092] 56 parts by mass of nickel particles, 40 parts by mass of terpineol, 4 parts by mass of ethyl cellulose (molecular weight 140,000), and 1 part by mass of benzotriazole were kneaded with a triple roll to form a paste, thereby preparing a paste for internal electrode layers.
[0093] Then, the dielectric layer paste prepared above was used to form a green sheet on a PET film, and the internal electrode layer paste was screen-printed to form a green sheet.
[0094] A plurality of green sheets were laminated and pressure-bonded to form a green laminate, and the green laminate was cut to a predetermined size to obtain a green chip.
[0095] The obtained green chip was subjected to a binder removal process, fired in a reducing atmosphere, and further annealed to obtain a sintered body (dielectric composition) fired in a reducing atmosphere. The firing conditions were a temperature rise rate of 200°C / h, a holding temperature of 1250°C, and a holding time of 2 hours. The atmospheric gas was a mixed gas of nitrogen and hydrogen (hydrogen concentration 3%) humidified to a dew point of 20°C. The annealing conditions were a holding temperature of 1050°C, and a holding time of 2 hours. The atmospheric gas was nitrogen gas humidified to a dew point of 20°C.
[0096] The end faces of the element body 10 obtained as described above were polished, and an external electrode paste was applied and baked to form the external electrodes 4.
[0097] In this manner, a multilayer ceramic capacitor 1 (hereinafter referred to as a "capacitor sample") was obtained.
[0098] < Observation of main phase particles > In a field of view of 1.7 μm×1.7 μm on the cross section of the dielectric composition of the obtained capacitor sample, the main phase particles 20 were identified by STEM, and the main components of the main phase particles 20 were identified by EDS. The results are shown in Tables 1, 2 and 4.
[0099] < Observation of segregated particles > In a field of view of 1.7 μm×1.7 μm on the cross section of the dielectric composition of the obtained capacitor sample, heterogeneous phases were identified by STEM, and the amounts of Y, Mg and Ti were measured by EDS.
[0100] When Y, Mg and Ti are present at the same position, the total of Y, Mg and Ti is 70 molar parts or more when the total of the metal elements contained in the heterogeneous phase is taken as 100 molar parts, and Mg / (RE+Mg) is 0.1 to 0.3, the heterogeneous phase is determined to be RE-Mg-Ti-O segregated particles 22. The presence or absence of RE-Mg-Ti-O segregated particles 22, and the results of Ti / (RE+Mg) and Mg / (RE+Mg) are shown in Tables 1, 2 and 4. It was confirmed that in each capacitor sample having RE-Mg-Ti-O segregated particles 22, the RE-Mg-Ti-O segregated particles 22 are present at the grain boundaries 28 of the main phase particles 20.
[0101] < 320℃ thermal shock test > The capacitor samples were immersed in flux in a solder bath heated to 320°C, and then held with tweezers and immersed in the solder bath. The capacitor samples were then removed and ultrasonically cleaned with thinner, after which their appearance was observed. This test was performed on 20 capacitor samples. The number of capacitor samples that had cracks is shown in Tables 1, 3, and 5.
[0102] < Average particle size > The average grain size was measured for each sample in Tables 3 and 5. Specifically, the cross section of the dielectric composition was measured to obtain a total of 5 μm 2 After the above observations, the circle equivalent diameters of the observed Y-Mg-Ti-O segregated particles 22 were measured, and the measured values were averaged to obtain the average particle size of the Y-Mg-Ti-O segregated particles 22. The results are shown in Tables 3 and 5.
[0103] < 350℃ thermal shock test > A 350°C thermal shock test was conducted on each sample in Tables 3 and 5. Specifically, the capacitor sample was immersed in flux, and then held with tweezers and immersed in a solder bath heated to 350°C. The capacitor sample was then removed and ultrasonically cleaned with thinner, after which its appearance was observed. This test was conducted on 20 capacitor samples. The number of capacitor samples that had cracks is shown in Tables 3 and 5.
[0104] < 380℃ thermal shock test > A 380°C thermal shock test was conducted on each sample in Tables 3 and 5. Specifically, the capacitor sample was immersed in flux, and then held with tweezers and immersed in a solder bath heated to 380°C. The capacitor sample was then removed and ultrasonically cleaned with thinner, after which its appearance was observed. This test was conducted on 20 capacitor samples. The number of capacitor samples that had cracks is shown in Tables 3 and 5.
[0105] < Average particle number > The average particle number was measured for each sample in Table 5. Specifically, the cross section of the dielectric composition A total of 5 μm 2 The average number of observed RE-Mg-Ti-O segregated particles 22 was calculated based on the above observations. The results are shown in Table 5.
[0106] < Dielectric constant > The dielectric constant was measured for each sample in Table 5. Specifically, a signal with a frequency of 1 kHz and an input signal level (measurement voltage) of 1 Vrms was input to the capacitor sample at room temperature (20°C) using a digital LCR meter (4284A manufactured by YHP), and the capacitance C was measured. The dielectric constant was then calculated based on the thickness of the sintered body, the effective electrode area, and the capacitance C obtained as a result of the measurement. The results are shown in Table 5.
[0107] [Table 1]
[0108] [Table 2]
[0109] [Table 3]
[0110] [Table 4]
[0111] [Table 5]
[0112] From Table 1, it was confirmed that when the dielectric composition contained RE-Mg-Ti-O segregated particles (sample numbers 5 to 7, 9, and 10), the results of the 320°C thermal shock test were better than those when the dielectric composition did not contain RE-Mg-Ti-O segregated particles (sample numbers 1 to 4 and 8). [Explanation of symbols]
[0113] 1. Multilayer ceramic capacitor 10... Element body 2... Dielectric layer 20… Main phase particles 22… RE-Mg-Ti-O segregated particles 28… Grain boundary 3… Internal electrode layer 4… External electrode
Claims
1. A dielectric composition comprising main phase particles and segregated particles, at least a part of the segregated particles is an RE-Mg-Ti-O segregated particle containing an RE element, Mg, Ti and O, The RE element is a rare earth element, when the total amount of metal elements in the RE-Mg-Ti-O segregated particles is 100 parts by mol, the total amount of the RE element, Mg and Ti in the RE-Mg-Ti-O segregated particles is 70 parts by mol or more, A dielectric composition, wherein the ratio of Mg to the total of the RE element and Mg in the RE-Mg-Ti-O segregated particles is 0.1 to 0.
3.
2. 2. The dielectric composition according to claim 1, wherein the RE-Mg-Ti-O segregated grains are present at grain boundaries of the main phase grains.
3. 2. The dielectric composition according to claim 1, wherein the RE-Mg-Ti-O segregated particles have an average particle size of 0.1 μm or less.
4. The cross section of the dielectric composition is 5 μm in total. 2 When the above observations were made, the RE-Mg-Ti-O segregated particles were found to have an average size of 0.2 to 2 particles / μm 2 The dielectric composition according to claim 1, wherein
5. The composition of the main phase particles is BaTiO 3 The dielectric composition according to claim 1 ,
6. The composition of the RE-Mg-Ti-O segregated particles is {RE (1-a) Mg a } 2 Ti 2 O 7 and 2. The dielectric composition according to claim 1, wherein a is 0.1 to 0.
3.
7. An electronic component comprising the dielectric composition according to any one of claims 1 to 6.
Citation Information
Patent Citations
Ceramic capacitor and its manufacture
JP2001006966A